Impact of Cooking Procedures on Coccidiostats in Poultry Muscle - Rui R. Martins; André M. P. T. Pereira; Liliana J. G. Silva; Sofia C. Duarte; Andreia Freitas; Angelina Pena (Antibiotics)
Background/Objectives: Poultry meat is a popular and nutritious food, valued for its high protein content and healthy fat profile. However, like other animal products, it can contain pharmaceutical residues, including coccidiostats, antimicrobials commonly used to prevent parasitic infections caused by Eimeria species. While most monitoring focuses on raw meat, it is important to understand how these compounds behave during cooking to assess potential health risks better and ensure food safety. Methods: This study examined how five different cooking methods (roasting, grilling, and microwaving, beer and wine marinating) affect the levels of eight coccidiostat residues in 45 samples of poultry muscle collected from a supermarket located in the center of mainland Portugal from May to July 2024. After applying different cooking procedures, ionophore and synthetic coccidiostat residue levels were measured using solid–liquid extraction followed by ultrahigh-performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS). Results are expressed as percentages of the original concentrations: 100% indicates stability, values above 100% suggest a relative increase (often due to moisture loss), and values below 100% reflect a decrease, likely from heat degradation. Results: Roasting, grilling, and microwaving all increased residue concentrations—up to 198.5%, 180.1%, and 158.4%, respectively. In contrast, marinating meat in wine or beer before cooking reduced residues to 73.1% and 72.0%, suggesting a mitigating effect. The initial concentration also influenced the outcome: samples fortified at the maximum residue limit (MRL) had an overall higher mean concentration after cooking (148.3%,) than those fortified at twice the MRL (2 MRL), which averaged 124.5%. Conclusions: These results show that cooking can significantly alter coccidiostat residue levels depending on the cooking procedures and initial concentration. Ongoing monitoring and further research are essential to better understand how cooking affects these residues and their by-products. This knowledge is key to improving food safety practices and refining consumer health risk assessments.